MENGUBAH KELEMAHAN MENJADI PELUANG KEPEMIMPINAN TRANSFORMATIF KEPALA SEKOLAH: CHANGING WEAKNESS INTO OPPORTUNITY SCHOOL PRINCIPAL TRANSFORMATIONAL LEADERSHIP - Riatri, Dian Perdana (Satya Widya, 2023)
SD Sidorejo Lor 02 Salatiga is facing two difficulties in the same time, school yard and students’ report. School principal conducted an innovation in making student report application which is shows a good progress and result and submit DAK proposal for paving construction program. The proposal wasn’t accepted but the school can’t wait any longer so SD Sidorejo Lor 02 decided to do the construction independently. This is qualitative descriptive research. The data is collected through interview. The result shows that transformational leadership by the school principal able to change school’s weakness into opportunity. Students’ report application can be used for one of fund-raising source to support schools’ yard paving block construction.